نماذج تمويل التنمية الاقتصادية في الجماهيرية - جمعة ميلود (Dirasat in Economics and Business, 1984)
In his article we try to discover how Leer mic development is being financcd in Libyan economy following the tradi lonal classification of finance into inter.al and external finance. Using a newly coastracted flow-c! Cand account the Libyan economy in 1517 Logether with information about the retudes of national income saving ud investment for the period 106 1010 WC lyve kuluded that: As a result of the non-existence of de financial instruments and institutiens otser then commercial banks to gether with the tendency of these banks to keep a high percentage of their assets in a liquid form and the persistence of the public of keeping a high percentage of their money holdings in terms of currency, the lending-borrowing activity through financial Intermediation in the Libyan economy has become very limited and consequently the concept of external finance of cconomic develop ment, which in turn has resulted in a high dependence of economic development on internal finance instead. The dominance of internal finance techniques and the appearant reluctance of the government, financial institutions and the public in engaging in external finance practices has led in our view to an underutilization of funds available for economic developrient programes in the Libyan economy as well as directing a substantial proportion of national savings to consumption commc dities especially those of durable nature because of the lack of investement opportunities for small savers in particular who otherwise would have invested in the financial market (stocks and bonds) This situation calls, in our opinion, for a culin steps of reform to be taken which can be summarized as follow: The commercial barking sector must be reorganized to take a more positive role in financing economie deurlopment projects and attracting more funds especia lly from small savers. 2 The creation of a capital market instuursents and institutions (stocks and bonds) which can provide a long term finance for invest ments which commercial banks can not finance. 3. Mere emphasis must be given to the Inancial aspects of economic development ie. together with lis. ting all the projects to be undertaken by an economic development plan a detailed study of fisancial resources for this plan should be introduced and clearly indicating the role of alternative sources of finance.